KAJIAN HUKUM TERHADAP TINDAKAN ABORSI ILEGAL - I Made Dwika Widhitama; Sujono (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2025)
Legal protection for victims of illegal abortion, focusing on the case of forced abortion allegedly carried out by police officer Ipda YF. Illegal abortion violates the right to life and the laws and regulations in Indonesia, namely the old Criminal Code (Law No. 1 of 1946) and the Health Law (currently Law No. 17 of 2023), which generally prohibit abortion except for emergency medical indications or rape. The new Criminal Code (Law No. 1 of 2023), clarifies the expansion of the legal subjects of abortion perpetrators and explicitly regulates exceptions to abortion. This study uses a normative legal method with a statutory approach. The results show that the case of Ipda YF highlights the importance of strict criminal law enforcement (especially Article 347 of the old Criminal Code or Article 463 of the new Criminal Code for forced abortion) and maximum disciplinary/ethical sanctions for law enforcement officers who abuse their authority. Protection of victims of illegal abortion must be comprehensive, including protection from threats and intimidation (through LPSK), medical and psychological recovery, and the right to restitution/compensation.